KURVA PERTUMBUHAN MIKROALGA PADA MEDIA AIR GAMBUT SEBAGAI RANCANGAN LKPD MATERI PROTISTA KELAS X SMA - Nur Ahyana; Zulfarina Zulfarina; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the growth of microalgae in peat water media and produce a design of Student Worksheet (LKPD) protists in class X high school. This research was carried out in the Biology Education Laboratory FKIP UNRI in March-April 2019. This research was conducted in two stages, namely the experimental stage: microalgae growth in the peat water medium of Giam Siak Kecil Bukit Batu Biosphere Reserve and the design phase of the LKPD: analysis of potential material material development class X high school protists. The study used an experimental method with Completely Randomized Design (CRD) consisting of 3 treatments and 3 replications. The parameter in this study is Optical Dencity (OD). Based on the results of Analysis of Variance (ANAVA) at the level of 5%, the addition of microalgae in the media of peat water significantly affected the OD values of microalgae. The best combination of treatments is found in treatment M1 with a mean OD value of 0.115 achieved on the seventh day. While based on the analysis of potential results of the study can be used as a draft Student Worksheet (LKPD) material for class X high school protists in KD 3.6.Key Words: Growth Curve, LKPD, Microalgae.